IMF programs and borrowing costs: Does size matter? - Salim Chahine; Ugo Panizza; Guilherme Suedekum (Graduate Institute of International and Development Studies, 2024)
This paper studies whether IMF programs and their size affect borrowing costs by comparing the coupon of bonds issued around an IMF arrangement. By comparing bonds issued immediately before the inset of the program with bonds issued immediately after the program, we show that, on average, the approval of the program leads to a 72-basis points reduction in borrowing costs and program size matters. Our point estimates indicate that when program size increases by one percent of GDP, borrowing costs decrease by 23 basis points. We also show that program size only matters for ex-post programs (i.e., those implemented during crises). For precautionary ex-ante programs, borrowing costs increase with program size. However, the effect of program size is small and, therefore, ex-ante programs never lead to a statistically significant increase in borrowing costs and in most cases lead to a significant reduction in borrowing costs.
Keywords: F22; F33; F34; G01; G15; 330; IMF programs; Sovereign debt; Bond yields; International financial markets